2023
DOI: 10.1038/s41598-023-43982-2
|View full text |Cite
|
Sign up to set email alerts
|

PFKP is a prospective prognostic, diagnostic, immunological and drug sensitivity predictor across pan-cancer

Jian Peng,
Pingping Li,
Yuan Li
et al.

Abstract: Phosphofructokinase, platelet (PFKP) is a rate-limiting enzyme of glycolysis that plays a decisive role in various human physio-pathological processes. PFKP has been reported to have multiple functions in different cancer types, including lung cancer and breast cancer. However, no systematic pancancer analysis of PFKP has been performed; this type of analysis could elucidate the clinical value of PFKP in terms of diagnosis, prognosis, drug sensitivity, and immunological correlation. Systematic bioinformation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(109 reference statements)
1
1
0
Order By: Relevance
“…Thirdly, the oncogenic role of PFKP was confirmed by organoids and PDX models in HNSCC. Our findings, along with others [ 11 , 42 ], indicate that PFKP may be a pivotal factor in HNSCC tumorigenesis and progression, making it a potential therapeutic target for HNSCC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thirdly, the oncogenic role of PFKP was confirmed by organoids and PDX models in HNSCC. Our findings, along with others [ 11 , 42 ], indicate that PFKP may be a pivotal factor in HNSCC tumorigenesis and progression, making it a potential therapeutic target for HNSCC.…”
Section: Discussionsupporting
confidence: 82%
“…PFKP is the predominant isoform of PFK-1 in various types of tumors [ 8 10 ]. Upregulation of PFKP is strongly associated with tumor progression and is a significant indicator of an unfavorable prognosis in breast cancer, glioblastoma, and leukemia [ 8 , 10 , 11 ]. A substantial body of research has demonstrated the critical role of PFKP in promoting aerobic glycolysis within cancer cells, consequently driving cancer cell proliferation and metastasis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%